The Influence of Effective Communication and Patient Safety Culture on Physician Behavior in Filling Out Medical Records with Work Engagement as an Intervening Variable in a Type B Private Hospital in West Jakarta - Andani, Evi; Hosizah; Mutiara, Rina (Al Makki Publisher, 2024)
This research is based on doctors' disciplinary problems in filling in complete patient medical record data, which has caused several patient safety incidents to occur. The aim of this research is to empirically reveal the influence of effective communication and patient safety culture on doctor behavior with work engagement as an intervening variable. This research is included in quantitative research with a causality approach, the population used is doctors, the sampling technique uses purposive sampling with determining the number of samples using the Slovin formula with an error rate of 5%, so that a sample size of 97 respondents is obtained, with a sampling technique using non-probability sampling . The analysis method uses the three box method and PLS-SEM with the help of the samrt-PLS program. The results of the analysis conclude that work engagement positively intervenes in the influence of effective communication and patient safety culture on doctor behavior, effective communication and patient safety culture have a positive and significant effect on work engagement and doctor behavior, and work engagement is able to influence doctor behavior positively and significant, and also dominates its influence compared to effective communication and patient safety culture.